(untitled) (Educational Dimension, 2021)
In this study, the issues of contemporary IT specialists training in terms of constant innovation and rapid expansion of computing are examined in the context of synchronized curriculum shaping. The authors’ curriculum simulation technique, which uses Petri nets, is shown. Some didactical foundations of curriculum design and academic discipline structure, as well as the theoretical basics of Petri nets in terms of their considerable facilities for multiple processes synchronization, formed the theoretical framework that allowed us to develop the technique. The technique of academic disciplines structuring based on the frame model of knowledge representation is described as a series of processes that culminate in a net of disciplines modules (frames) that include the appropriate learning materials while preserving and propagating links between them. The practical-driven approach to curriculum modeling based on Petri nets simulation is offered to tackle the problem of synchronization of learning elements mastery across academic disciplines with regard to the established links in the frames. The many types of precedence relations for the learning elements (frame inputs and outputs) were identified. Using these precedence relations, we were able to model a learning element and the process of mastering it using Petri nets. We were able to create a model of a curriculum discipline module and, eventually, a curriculum discipline model using Petri nets modifications and learning element connections of various types. All of the evolution of the learning elements mastering by students in the curriculum courses is represented by built Petri nets models. The rules of Petri net execution and alterations ensure that their mastering is synchronized. The advantages and disadvantages of the proposed technique are discussed. The advantages of using such a simulation to create a synchronized curriculum for IT-specialist training are outlined. The research’s potential are presented in terms of applying the findings to the development of specialized software.